Step
*
2
1
of Lemma
ravg-dist-when-rleq
1. x : ℝ
2. y : ℝ
3. x ≤ y
4. (ravg(x;y) - x) = ((r1/r(2)) * (y - x))
5. |ravg(x;y) - x| = ((r1/r(2)) * |y - x|)
6. |y - ravg(x;y)| = ((r1/r(2)) * |y - x|)
7. (x ≤ ravg(x;y)) ∧ (ravg(x;y) ≤ y)
⊢ (y - ravg(x;y)) = ((r1/r(2)) * (y - x))
BY
{ (RWO "rabs-of-nonneg" (-2) THEN Auto) }
Latex:
Latex:
1.  x  :  \mBbbR{}
2.  y  :  \mBbbR{}
3.  x  \mleq{}  y
4.  (ravg(x;y)  -  x)  =  ((r1/r(2))  *  (y  -  x))
5.  |ravg(x;y)  -  x|  =  ((r1/r(2))  *  |y  -  x|)
6.  |y  -  ravg(x;y)|  =  ((r1/r(2))  *  |y  -  x|)
7.  (x  \mleq{}  ravg(x;y))  \mwedge{}  (ravg(x;y)  \mleq{}  y)
\mvdash{}  (y  -  ravg(x;y))  =  ((r1/r(2))  *  (y  -  x))
By
Latex:
(RWO  "rabs-of-nonneg"  (-2)  THEN  Auto)
Home
Index